Lactobacillus plantarum KFY02 enhances the prevention of CCl4-induced liver injury by transforming geniposide into genipin to increase the antioxidant capacity of mice. (October 2020) - Pan, Yanni; Wang, Hong; Tan, Fang; Yi, Ruokun; Li, Wenfeng; Long, Xingyao; Mu, Jianfei; Zhao, Xin
Graphical abstract: Highlights: Geniposide is partially converted into genipin by Lactobacillus plantarum KFY02. Lactobacillus plantarum KFY02 reduce the liver damage in mice by converting geniposide to genipin. Lactobacillus plantarum KFY02 enhance the antioxidant capacity of the body by converting geniposide to genipin. Abstract: This study investigated Lactobacillus plantarum KFY02 (KFY02) and its ability to enhance the antioxidant capacity of the body by converting geniposide to genipin, thereby decreasing the liver damage induced by CCl4 in mice. The experimental results showed that geniposide is partially converted into genipin by KFY02. In liver-injured mice, KFY02 and geniposide could decrease the liver index, the AST, ALT, TG, and MDA serum levels, and the levels of cytokines IL-6, IL-12, TNF-α, and IFN-γ while up-regulating SOD and GSH-Px levels. KFY02 and geniposide increased the mRNA and protein expression of Mn-SOD, Cu/Zn-SOD, CAT, GSH-Px, and IκB-α and decreased the mRNA and protein expression of COX-2, iNOS, and NF-κB in the liver tissue of liver-injured mice. In summary, the conversion of geniposide to genipin by L. plantarum KFY02 can effectively enhance the body's antioxidant capacity to prevent CCl4 -induced liver damage in mice.